AB0896 Association of iga antibodies against cd74 with production of il17a but not of tnfalpha in patients with active axial spondyloarthritis. (12th June 2018) - Baraliakos, X.; Kniesch, K.; Baerlecken, N.; Braun, J.; Witte, T.
Abstract : Background: Axial spondyloarthritis (axSpA) is strongly associated with HLA-B27. Recently, IgA antibodies (Abs) against CD74 (IgA-anti-CD74) and T-cells carrying CD-74-specific T-cell receptors were also found to be associated with axSpA, especially in patients with ankylosing spondylitis, the radiographic form of axSpA. Tumour necrosis alpha (TNFα) inhibitors and IL-17 antagonists are efficacious in patients with active axSpA. Objectives: To investigate whether IgA-anti-CD74 Abs are associated with pro-inflammatory cytokines in the sera of patients with HLA-B27-positive and -negative patients with active axSpA. Methods: Blood samples of 62 HLA-B27-positive and 58 HLA-B27-negative patients with axSpA (44% AS) prior to starting a biologic therapy were collected. A cytometric bead-array (CBA Flex Set) was used to measure serum levels of interleukin (IL)−17A, IL-6, IL-1α, TNFα, and interferon (INF)-γ. IgA-anti-CD74 Abs were measured by ELISA, using the predefined cut-off of 15 U/ml. Their mean concentrations were compared between groups using T-tests. The patients who were positive or negative for IgA-anti-CD74 Abs were compared using chi-square test. Results: IgA-anti-CD74 Abs were detected in 54/120 axSpA patients (45%). There were no differences in the baseline demographics and clinical assessments in patients with or without IgA-anti-CD74 Abs. The presence of IgA-anti-CD74 Abs was associated with higher serum concentrations of IL-17A (p=0.01), irrespective of the presence of HLA-B27, CRP and IL-6 (both p<0.05) but not TNFa (p=0.2). Conclusions: In a cross-sectional study, the presence of IgA Abs against CD74 was associated with serum levels of pro-inflammatory biomarkers such as CRP (and IL-6) and IL-17 but not TNFa irrespective of HLA-B27 status. Longitudinal prospective studies are needed to show that the measurement of IgA anti-CD74 Abs and/or serum cytokines can help to guide treatment decisions. Acknowledgements: We thank Novartis Pharma AG for the support of our study. Disclosure of Interest: X. Baraliakos: None declared, K. Kniesch: None declared, N. Baerlecken: None declared, J. Braun: None declared, T. Witte Grant/research support from: Novartis